Doses de zinco em diferentes condições de acidez de um solo de cerrado. II. Nível crítico na planta - Buzetti, S. (1991)
In this work it was demanded to verify the zinc critical levels in soybean plants cultivated in a Dark-Red Latosol. So the experiment was carried out in vases with 4 liters of soil, which has received five doses of Zn (0, 1.0, 2.0, 3.0 and 4.0 ppm) in three correction levels. It was verified that the critical levels of the nutrient in plant (for 90% from highest production) was between 36 and 53 ppm to the dry matter yield and grains in treatments with correction.